Methanolic Extract of Peel of Citrus maxima Fruits Exhibit Analgesic, CNS Depressant and Anti-inflammatory Activities in Swiss Albino Mice - Ibrahim, Md.; Amin, Mohammad Nurul; Millat, Md. Shalahuddin; Raju, Jahangir Alam; Hussain, Md. Saddam; Sultana, Farhana; Islam, Md. Monirul; Hasan, Md. Murad (Biology, Engineering, Medicine and Science Reports)
Objectives: This study investigates analgesic, CNS depressant and anti-inflammatory activi- ties of crude methanolic extract of Peel of Citrus maxima fruits. Materials and Methods: Methanolic extracts of Citrus maxima peel with different concentration were tested for an- algesic activity in mouse model of acetic acid induced writhing and formalin induced licking and biting. Anti-inflammatory effect was tested by carrageenan induced paw edema model and the CNS depressant activity was evaluated by observing the reduction of locomotors activity by hole cross and open field test. Results: The extract, at 500 mg/kg, showed higher analgesic activity (73.34%) against acetic acid induced pain in mice while the standard ref- erence drug Diclofenac sodium exhibited 87.13% activity at 10 mg/kg dose. The test dose at 500 mg/kg produced 48.23% protection in formalin induced hind paw licking and biting compared to 54.11% protection by the reference drug (10 mg/kg Diclofenac sodium). The anti- inflammatory effect of the extract was comparable to reference drug Ibuprofen and the effect was sustained for 2-4 hr. However, the extract also showed significant dose dependent CNS depressant activity. Conclusion: Methanolic extract of peel of Citrus maxima fruits has CNS depressant effect with moderate analgesic and anti-inflammatory properties.
Keywords: Analgesic; Anti-inflammatory; CNS activity; Citrus maxima